Relationships between changes in leptin and insulin resistance levels in obese individuals following weight loss - Tsu-Nai Wang; Wen-Tsan Chang; Yu-Wen Chiu; Chun-Ying Lee; Kun-Der Lin; Yu Yao Cheng; Yi-Ju Su; Hsin-Fang Chung; Meng-Chuan Huang (Kaohsiung Journal of Medical Sciences, 2013)
Obesity can augment insulin resistance (IR), leading to increased risk of diabetes and heart disease. Leptin, ghrelin, and various fatty acids present in the cell membrane may modulate IR. In this study, we aimed to investigate the impact of weight loss on IR, serum leptin/ghrelin levels, and erythrocyte fatty acids, and studied the associations between changes in these variables. A total of 35 obese (body mass index ≥ 27) adults participated in a weight loss program for 3 months. IR was assessed using homeostasis model assessment for insulin resistance (HOMA-IR). The obese participants had a mean weight loss of 5.6 ± 3.8 kg followed by a 16.7% and 23.3% reduction in HOMA-IR and leptin (p < 0.001) levels, and an 11.3% increase in ghrelin levels (p = 0.005). The level of erythrocyte saturates decreased by 2.8%, while the level of n–3 polyunsaturates increased by 16.8% (all p < 0.05). The changes in leptin levels (−5.63 vs. −1.57 ng/mL) were significantly different (p = 0.004) in those with improved IR (changes in HOMA-IR < 0) than those without improvement (changes in HOMA-IR ≥ 0), though there were no differences in the changes of ghrelin (p = 0.120) and erythrocyte fatty acids (all p > 0.05) levels. After adjusting for age, gender, changes in ghrelin, and body fat, we found a significant correlation between decreases in leptin and less risk of no improvement in HOMA-IR levels [odds ratio (OR) = 0.69, p = 0.039]. In conclusion, a moderate weight reduction in obese participants over a short period significantly improved IR. This weight reduction concomitantly decreased serum leptin, increased ghrelin, and elevated some erythrocyte unsaturates. Only leptin correlated independently with IR improvement upon multivariable logistic regression analysis, which indicates that leptin may play a role in the modulation of IR following weight loss.